Hydrothermal Synthesis of High-Performance 3D Black TiO2/rGO Solar Absorber for Solar-Driven Interfacial Water Evaporation - Wesley J. Lawrence; Fisseha A. Bezza; Shepherd M. Tichapondwa; Evans M. N. Chirwa (Chemical Engineering Transactions, 2025)
Fresh water around the globe has become a resource which is in short supply, and this is being further aggravated by rapid economic and population growth, industrialisation, and urbanisation. Desalination has long been realised as a solution to the fresh water crisis and implementation has swiftly increased. Traditional solar-driven desalination technologies are extremely inclined to low efficiencies due to the dissipation of solar energy into the non-evaporative bulk water. Solar-driven interfacial water evaporation hinges on the principle of heat localisation at the water-air interface which in turn leads to extraordinary photothermal conversion potential and water evaporation rates. This study aims to demonstrate the potential of high-performance solar energy utilisation through the development of a highly efficient solar absorber. By hydrothermally reducing a graphene oxide (GO) suspension containing black titanium dioxide (black TiO2) particles, a 3D hybrid solar absorber can be fabricated. The 3D hybrid composite was characterised using various techniques to evaluate its structure and morphology, surface area, and solar absorption potential. The solar-driven interfacial water evaporation system demonstrated a high photothermal conversion efficiency of 82.38 % when exposed to 1-sun illumination and an evaporation rate of 1.19 kg/m2·h. The encouraging performance displayed by the 3D solar absorber is owed to the high optical absorption of the whole UV and visible wavelength region.